WASH for child health: Some evidence in support of public intervention in the Philippines - Joseph J. Capuno; Carlos Antonio R. Tan; Xylee Javier (University of the Philippines, School of Economics (UPSE), 2016)
Like in many developing countries, diarrheal diseases remain a top cause of child mortality and morbidity in the Philippines. Partly to address this problem, the government has undertaken programs to expand access to safe water and sanitation facilities, especially among poor households. To assess the impact of such interventions on child health, we apply propensity score matching technique on the pooled data from the last five rounds of the National Demographic and Health Survey. We find that improved water and improved sanitation each reduced the probability of child diarrhea in 1993-2008 by around two percentage points. In 2013, improved water reduced the probability by about 7 percentage points, while improved sanitation do not seem to have statistically significant effect. These results lend support to the government's programs to widen access to safe water and sanitation facilities as measures to improve child health.
Keywords: I12; I18; O53; 330; water and sanitation; child health; Philippines